A Yeast-Based Functional Assay to Study Plant N-Degron – N-Recognin Interactions - Kozlic, Aida; Winter, Nikola; Telser, Theresia; Reimann, Jakob; Rose, Katrin; Nehlin, Lilian; Berckhan, Sophie; Sharma, Gunjan; Dambire, Charlene; Boeckx, Tinne; Holdsworth, Michael J.; Bachmair, Andreas (Frontiers in Plant Science, 2022)
The N-degron pathway is a branch of the ubiquitin-proteasome system where amino-terminal residues serve as degradation signals. In a synthetic biology approach, we expressed ubiquitin ligase PRT6 and ubiquitin conjugating enzyme 2 (AtUBC2) from Arabidopsis thaliana in a Saccharomyces cerevisiae strain with mutation in its endogenous N-degron pathway. The two enzymes re-constitute part of the plant N-degron pathway and were probed by monitoring the stability of co-expressed GFP-linked plant proteins starting with Arginine N-degrons. The novel assay allows for straightforward analysis, whereas in vitro interaction assays often do not allow detection of the weak binding of N-degron recognizing ubiquitin ligases to their substrates, and in planta testing is usually complex and time-consuming.